Fatty acid‐releasing activities in Sinorhizobium meliloti include unusual diacylglycerol lipase. (27th March 2015) - Sahonero‐Canavesi, Diana X.; Sohlenkamp, Christian; Sandoval‐Calderón, Mario; Lamsa, Anne; Pogliano, Kit; López‐Lara, Isabel M.; Geiger, Otto
Summary Phospholipids are well known for their membrane‐forming properties and thereby delimit any cell from the exterior world. In addition, membrane phospholipids can act as precursors for signals and other biomolecules during their turnover. Little is known about phospholipid signalling, turnover and remodelling in bacteria. Recently, we showed that a FadD‐deficient mutant of Sinorhizobium meliloti, unable to convert free fatty acids to their coenzyme A derivatives, accumulates free fatty acids during the stationary phase of growth. Enzymatic activities responsible for the generation of these free fatty acids were unknown in rhizobia. Searching the genome of S. meliloti, we identified a potential lysophospholipase (SMc04041) and two predicted patatin‐like phospholipases A (SMc00930, SMc01003). Although SMc00930 as well as SMc01003 contribute to the release of free fatty acids in S. meliloti, neither one can use phospholipids as substrates. Here we show that SMc01003 converts diacylglycerol to monoacylglycerol and a fatty acid, and that monoacylglycerol can be further degraded by SMc01003 to another fatty acid and glycerol. A SMc01003‐deficient mutant of S. meliloti transiently accumulates diacylglycerol, suggesting that SMc01003 also acts as diacylglycerol lipase (DglA) in its native background. Expression of the DglA lipase in Escherichia coli causes lysis of cells in stationary phase of growth.